Chestnut-like SnO2/C nanocomposites with enhanced lithium ion storage properties. (December 2016) - Yang, Lie; Dai, Tao; Wang, Yuecun; Xie, Degang; Narayan, R. Lakshmi; Li, Ju; Ning, Xiaohui
Abstract: Chestnut-like SnO2 and SnO2 /C nanocomposites with hierarchical structures are synthesized by hydrothermally oxidizing Sn nanoparticles in glucose solution. Structural characterizations using SEM and TEM reveal that the SnO2 nanoparticles are composed of numerous, randomly arranged SnO2 nanosheets with hollow cores. Owing to the short electron and ion diffusion distances and transformation strain accommodation mechanism of this structure the new SnO2 /C nanocomposites exhibit enhanced lithium ion storage properties with a capacity of 930 mAh g −1 and capacity retention of about 96% after 100 cycles at 0.1 C. An in situ TEM study of the electrochemically driven lithiation/delithiation of SnO2 /C nanocomposites reveals that their enhanced cycling stability is mainly facilitated by the limited volume expansion and excellent mechanical robustness of the hollow chestnuts. Graphical abstract: Highlights: Chestnut-like SnO2 nanoparticles are synthesized by oxidizing Sn nanoparticles in glucose solution. Nanoscale Kirkendall effect and oriented growth are supposed to contribute to the formation of chestnut-like structure. Chestnut-like SnO2 /C exhibits largely enhanced cycling stability. Limited volume expansion and excellent mechanical robustness facilitate the enhanced cycling stability.